Identification of MsHsp20 Gene Family in Malus sieversii and Functional Characterization of MsHsp16.9 in Heat Tolerance - Yang, Meiling; Zhang, Yunxiu; Zhang, Huanhuan; Wang, Hongbin; Wei, Tao; Che, Shiyou; Zhang, Lipeng; Hu, Baoquan; Long, Hong; Song, Wenqin; Yu, Weiwei; Yan, Guorong (Frontiers in Plant Science, 2017)
Heat shock proteins (Hsps) are common molecular chaperones present in all plants that accumulate in response to abiotic stress. Small heat shock proteins (sHsps) play important roles in alleviating diverse abiotic stresses, especially heat stress. However, very little is known about the MsHsp20 gene family in the wild apple Malus sieversii, a precious germplasm resource with excellent resistance characteristics. In this study, 12 putative M. sieversii Hsp20 genes were identified from RNA-Seq data and analyzed in terms of gene structure and phylogenetic relationships. A new Hsp20 gene, MsHsp16.9, was cloned and its function studied in response to stress. MsHsp16.9 expression was strongly induced by heat, and transgenic Arabidopsis plants overexpressing MsHsp16.9 displayed improved heat resistance, enhanced antioxidant enzyme activity, and decreased peroxide content. Overexpression of MsHsp16.9 did not alter the growth or development under normal conditions, or the hypersensitivity to exogenous ABA. Gene expression analysis indicated that MsHsp16.9 mainly modulates the expression of proteins involved in antioxidant enzyme synthesis, as well as ABA-independent stress signaling in 35S:MsHsp16.9-L11. However, MsHsp16.9 could activate ABA-dependent signaling pathways in all transgenic plants. Additionally, MsHsp16.9 may function alongside AtHsp70 to maintain protein homeostasis and protect against cell damage. Our results suggest that MsHsp16.9 is a protein chaperone that positively regulates antioxidant enzyme activity and ABA-dependent and independent signaling pathway to attenuate plant responses to severe stress. Transgenic plants exhibited luxuriant growth in high temperature environments.